PS5:96 Il-21 dependent granzyme b production of b-?cells is decreased in patients with lupus nephritis. (21st March 2018) - Rabani, M; Wilde, B; Hübbers, K; Kribben, A; Witzke, O; Dolff, S
Abstract : Objectives: B-cells play a crucial role in the pathogenesis of lupus nephritis. Recently, a separate subset has been discovered characterised by expression of Granzyme B. The aim of this study is to investigate this subset in patients with systemic lupus erythematosus especially in patients with lupus nephritis. Methods: Isolated peripheral blood mononuclear cells of patients with systemic lupus erythematosus (n=30) and healthy controls (n=21) were in vitro stimulated with CPG, IgG +IgM and IL-21. Patients were sub-grouped in patients with and without biopsy proven lupus nephritis. CD19 +B cells were analysed for intracellular Granzyme B expression by flow cytometry. Patients disease activity was assessed by systemic lupus erythematosus disease activity index (SLEDAI). Results: The strongest stimulus for Granzyme B secretion of CD19 +B cells was IgG +IgM in presence of IL-21. Patients with systemic lupus erythematosus had a significant decreased percentage of Granzyme B+CD19+B cells. This could be shown in particular for patients with active disease and with lupus nephritis. Conclusions: These data demonstrate that CD19 +B cells of patients with systemic lupus erythematosus are impaired to produce Granzyme B. This may contribute to an imbalanced B-cell regulation towards effector B-cells which might promote the development of lupus nephritis.